Inventory and exploration of orchid in Polewali Mandar, West Sulawesi, Indonesia - DWI MURTI PUSPITANINGTYAS (Society for Indonesian Biodiversity, 2019)
Sulawesi is the fourth largest island in Indonesia. Sulawesi is also a very unique island, possessing a very high biodiversity due to the location  on the Wallacea area, and constituting  mixing plants from Asia and Australia.  An inventory and exploration of orchid in Polewali Mandar Regency was conducted from  25 May to 13 June 2014 to determine and assess the orchid diversity in the area.   Orchid specimens were recorded and collected using a purposive random sampling method. A total of 60 accession numbers were collected in the study  area. These collections represent 22 genera and 51 species, consists of 41 epiphyte orchids species and 10 terrestrial orchids species.  Some species are wide distribute in Indonesia, few of them are only found in eastern part of Indonesia such as Wallacea region, and are even endemic to Sulawesi.  Luisia celebica Schltr. and Micropera sterrophylla (Schltr.) Garay are noted as endemic orchid to Sulawesi.  While Dendrobium bicaudatum Reinw. ex Lindl., Habenaria beccarii Schltr., Malaxis trigonopetala (J.J.Sm.) S.Thomas, Schuit. & de Vogel and Pinalia quinquangularis (J.J.Sm.) Ormerod are endemic to the Wallacea region mainly in Sulawesi and Moluccas. Among those  orchids found in the study, Dendrobium clavator  Ridl.,  Pinalia quinquangularis (J.J.Sm.) Ormerod, and Pinalia xanthocheila (Ridl.) W.Suarez & Cootes  are noted as new records in Sulawesi.  Many new records of orchids are still to be expected from Sulawesi.